Penyuluhan Pemberian Asi Eksklusif Bagi Bayi Usia 0-6 Bulan Di Kampung Tanjung Ilir Kelurahan Sayar Kota Serang - Tuti Yelvianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Exclusive breastfeeding is the primary and best source of nutrition for infants. The World Health Organization (WHO) strongly recommends exclusive breastfeeding due to its numerous benefits for infant growth, particularly during the first six months of life. However, the significance of breastfeeding is often not conveyed effectively to nursing mothers, resulting in many failing to exclusively breastfeed their babies and opting instead for formula milk or other types of food. One reason for this failure is the lack of information provided to mothers, which weakens their motivation to consistently provide exclusive breastfeeding to their babies aged 0-6 months. To address this issue, a counseling session was conducted in Sayar Subdistrict, Serang City, with 15 participants. The session employed a pre-test and post-test method using a questionnaire consisting of 10 questions to measure the participants' knowledge of exclusive breastfeeding. The assessment was divided into three categories: good knowledge, adequate knowledge, and poor knowledge. The pre-test results showed that 13% of participants had good knowledge, 20% had adequate knowledge, and 67% had poor knowledge. After the counseling session, the results improved significantly, with 87% of participants categorized as having good knowledge, 13% with adequate knowledge, and none in the poor knowledge category. With this improved understanding of exclusive breastfeeding, it is hoped that the participants will be able to implement exclusive breastfeeding for their babies.